Cost-benefit analysis on the development of Belum-Temenggor Ecological Corridor in Gerik, Perak - Ibrahim, Zahari; Tuan Ibrahim, Tuan Marina; Othman, Mohd Shahwahid (Sabah Forestry Department, 2014)
The Central Forest Spine (CFS) project has the mission to protect the nation's biodiversity by connecting CFS complex key to making it a vast area of forests stretching from north to south and East to the West of Peninsular Malaysia which involves the creation of 37 ecological corridors in Peninsular Malaysia. The CFS is estimated to cover a total area of 5.3 million hectares or 40% of Peninsular Malaysia's land area, of which 80% is Permanent Reserved Forest. To initiate the CFS Programme, the government has selected Primary Linkage 2 (PL2) Belum-Temengor Ecological Corridor (BTEC), Gerik, Perak as the first CFS project in Peninsular Malaysia. An initial allocation of RM 60 million was approved in April 2011 for the implementation of this project over the period 2012-2015. This study includes the evaluation of goods and services of forest resources as well as the intangible values of forests in ecological corridors CFS in Hulu Perak, the effects of the cost will be accepted by the state government in the event of the destruction of the environment, natural disasters and economic activities downstream as a result of not maintaining the ecological corridors and to analyse in terms of finance and economics in order to see the importance of the area to either maintain as preservation or developed for the commercial projects, and getting the net present value (NPV) in order to see the importance of land use for the project is needed to make this study successful. The objectives of the study are: (i) to analyse the information obtained by using scientific and econometrics methods to get the net present value (NPV), incremental net present value (INPV); (ii) to make a summary and an assessment of the study area based on the result analysis and the BTEC is already a popular tourism destination. Even without the Ecological Corridor project, the BTEC is already providing a benefit stream of RM21,562,311 per year. Eco-tourism and recreational services provided 7.9%, while the avoidance of human-wildlife conflicts and local communities dependence on NTFPs collection contributed another 2.5% and 2.4% respectively. The local businesses from tourism provided 87.3% of the total annual contributions of economic values. Non-use values of biodiversity conservation contributed 17.9%. The above benefits reported earlier are not realised now only but far into the future and these benefits could be accumulated by discounting the future values into the current period and summing them up to obtain the NPVWoP. Using a discounting rate of 5% and analysing a cash flow over 10 years, the NPVWoP of current status quo situation is MYR 294,975,034. The cost and benefit analysis showed that if the Forestry Department is capable of generating incomes through obtaining international interests to set carbon offset projects or through the REDD PLUS initiatives, the ecological corridor project is viable. The Forestry Department would have to seek international interests to obtain the carbon offset projects and REDD Plus to compensate for the cost of implementing conservation efforts undertaken.